The first bad man a novel - July, Miranda 1974- (Scribner, 2015)
"Here is Cheryl, a tightly-wound, vulnerable woman who lives alone, with a perpetual lump in her throat. She is haunted by a baby boy she met when she was six, who sometimes recurs as other people's babies. Cheryl is also obsessed with Phillip, a philandering board member at the women's self-defense nonprofit where she works. She believes they've been making love for many lifetimes, though they have yet to consummate in this one. When Cheryl's bosses ask if their twenty-one-year-old daughter, Clee, can move into her house for a little while, Cheryl's eccentrically ordered world explodes. And yet it is Clee...the selfish, cruel blond bombshell...who bullies Cheryl into reality and, unexpectedly, provides her the love of a lifetime. Tender, gripping, slyly hilarious, infused with raging sexual obsession and fierce maternal love, Miranda July's first novel confirms her as a spectacularly original, iconic, and important voice today, and a writer for all time. The First Bad Man is dazzling, disorienting, and unforgettable"..
Keywords: FICTION / Literary; FICTION / Contemporary Women; FICTION / Humorous; Middle-aged women -- Fiction; Man-woman relationships -- Fiction